2011
DOI: 10.2332/allergolint.10-oa-0234
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Epidemiological Study of 553 Patients with Chronic Rhinosinusitis in Japan

Abstract: Similar to the relationship between nasal allergy and asthma, CRSwNP may be applicable to the concept of "one airway, one disease".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
25
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 22 publications
4
25
0
4
Order By: Relevance
“…For example, a recent study showed that 23.1% of patients with CRS in Japan suffered from asthma. 65 Conversely, higher incidence of radiological abnormalities in paranasal sinuses was also seen in asthmatic patients. 66e68 An early study showed that patients with mild-to-moderate asthma had an 88% incidence of abnormal sinus computed tomography (CT) findings, while patients with severe steroiddependent asthma showed 100% abnormal sinus findings on CTscans.…”
Section: Presence and Characterization Of Comorbidity Of Chronic Rhinmentioning
confidence: 91%
“…For example, a recent study showed that 23.1% of patients with CRS in Japan suffered from asthma. 65 Conversely, higher incidence of radiological abnormalities in paranasal sinuses was also seen in asthmatic patients. 66e68 An early study showed that patients with mild-to-moderate asthma had an 88% incidence of abnormal sinus computed tomography (CT) findings, while patients with severe steroiddependent asthma showed 100% abnormal sinus findings on CTscans.…”
Section: Presence and Characterization Of Comorbidity Of Chronic Rhinmentioning
confidence: 91%
“…It is undeniable that this may also reflect a lack of international consensus for defining tissue eosinophilia. While some groups define eosinophilia as an absolute number of eosinophils (five to eight) per random high powered field,3 5 6 others use a cut-off percentage of eosinophils (5–15%) for a number of high power fields counted in areas of greatest cellularity 7 8…”
mentioning
confidence: 99%
“…К 4 годам окончательно формируются гайморовы пазухи, поэтому увеличивается удельный вес верхнечелюстных синуси-тов. В связи с более поздним формированием фронталь-ных и сфеноидальных синусов их воспаление наблю-дается преимущественно у детей 7-12 лет, нередко встречается комбинированное поражение слизистой оболочки верхнечелюстных пазух и решетчатого лаби-ринта [7,[30][31][32].…”
unclassified
“…Для острых риносинуситов более характерна монофло-ра, микробные ассоциации встречаются, по разным дан-ным, в 10-30% всех случаев [19,29,31,32]. Основную роль в возникновении острого воспалительного процесса полости носа и околоносовых пазух в детском возрасте отводят S. pneumoniae (20-35%) и Н. influenzae (6-26%).…”
unclassified
See 1 more Smart Citation